2018
DOI: 10.1007/s10517-018-4207-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of HIF-1α- and HIF-2α-Immunopositive Neurons and Capillaries in Rat Cortex under Conditions of Tissue Hypoxia

Abstract: We measured the content of HIF-1α and HIF-2α-immunopositive neurons and microvessels in the brain of Wistar rats during the first 24 h of tissue hypoxia induced by subcutaneous injection of cobalt dichloride (50 mg/kg). In control rats (without hypoxia), immunohistochemical marker HIF-2α in cortex of parietal lobe was not detected, and HIF-1α was detected only in few weakly stained pale neurons and capillaries. In 30 min after injection of the cobalt salt, the number of HIF-1α neurons increased by 25.6% (in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Erlich et al reported that beclin-1 was expressed in neurons after exposure to hypoxia 4 and 24 h in mice, which was similar to our results [33]. Additionally, it was mentioned before that nucleus HIF1α might may regulate its target genes to promote a widespread adaptive response [20]. Guo reported that HIF1α may ameliorate brain damage during hypoxia through BNIP3-dependent augmentation of autophagic cell survival and reduction in cell apoptosis in rats [34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Erlich et al reported that beclin-1 was expressed in neurons after exposure to hypoxia 4 and 24 h in mice, which was similar to our results [33]. Additionally, it was mentioned before that nucleus HIF1α might may regulate its target genes to promote a widespread adaptive response [20]. Guo reported that HIF1α may ameliorate brain damage during hypoxia through BNIP3-dependent augmentation of autophagic cell survival and reduction in cell apoptosis in rats [34].…”
Section: Discussionsupporting
confidence: 90%
“…It was indicated neurons were more susceptible to hypoxia than glial cells. Moreover, Chertok et al and Hashemi et al pointed out that activation of HIF1α may regulate its target genes to promote a widespread adaptive response by increasing glucose transport, glycolysis, vascular growth, and cell survival [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The key role in this process has now been established to belong to the oxygen-sensitive transcription factor HIF-1α (Ju et al, 2016;Chertok and Kotsyuba, 2017). Researchers reported that HIF-1α are expressed in the central nervous system (CNS) of mammals (Mohindra et al, 2013;López-Hernández et al, 2012;Chertok et al, 2018). The current study reported that HIF-1α mRNA and protein were positive in all regions of yak and cattle telencephalon, which was consistent with other species.…”
Section: Discussionsupporting
confidence: 86%
“…The brain is one of the main organs of the body that strongly respond to acute hypoxia. [ 29 ] Hypoxia stimulates the expression of many genes, and 1 key protein involved is HIF-1, which is a transcription factor that regulates adaptive responses to the lack of oxygen in mammalian cells. HIF-1 consists of 2 proteins, HIF-1 alpha and HIF-1 beta.…”
Section: Roles Of Hif In Cerebral Hypoxiamentioning
confidence: 99%